Reactive Braking System - N, Nagendran; K S, Rani; P, Punitha; V P, Vaishnav; V, Balaji; S, Ragul (International Journal of Engineering and Technology, 2018)
This paper is based on the simplifying technique of the existing technology called Autonomous Emergency Braking (AEB) by using a simple electronic setup which can be easily installed in all the existing four-wheelers without changing its existing working system. By using this technology, the number of accidents due to human errors can be avoided in large scale for both the drivers and the pedestrians. This project aims to reduce the errors caused by the improper braking of the driver.Â Â